Terapia miofuncional en la parálisis cerebral - Cristina Jeannette, Galán Triviño (2020)
In this research work, the use Myofunctional Therapy is used in patients with oral motor disorders associated with Cerebral Palsy is analyzed, through the collection and analysis of scientific articles found in the different databases. Cerebral Palsy is a clinical condition which there is a lesion in the brain that is mainly characterized by motor and cognitive dysfunction; and other disorders depending on the severity and area of the brain where the injury occurred. It has been shown in studies that, in the population with this pathology, more than 50% have oral dysfunctions, being more likely when their motor damage is high. Myofunctional Therapy is a technique within speech therapy, which consists in rehabilitating the oral muscles, through active, passive exercises and sensory stimulation, of the compromised muscles; The mentioned therapy can be applied alone or in combination with another technique. The method of study was the collection of data, by searching for scientific articles in: Google Scholar, Pubmed, Science Direct, and World Wide Science, evaluating each article based on the ACC (Average Count Citation), the SJR (Scimago Journal Ranking) and with the PEDro assessment scale, thus obtaining 43 articles for the analysis of the results in this review. After analyzing the data of each scientific article, it was concluded that Myofunctional Therapy applied to oral disorders associated with cerebral palsy, is effective, although it is much more effective if combined with another muscle stimulation technique. After analyzing the data of each scientific article, it was concluded that Myofunctional Therapy applied to oral disorders associated with cerebral palsy, is effective, although it is much more effective if combined with another muscle stimulation technique.